Distance-based shared responsibility. (1st June 2020) - Temursho, Umed; Miller, Ronald E.
Abstract: This paper presents the global multi-regional extension of the upstream and downstream shared responsibility input-output (IO) frameworks and proposes to use distance-based sharing parameters in their applications. The extent of producers' control over production processes is approximated by the inverse (function) of the average distance of producers from primary inputs providers along the entire input demand chain. Similarly, the extent of producers' influence over advertising and sales is approximated by the inverse (function) of the average distance of producers from final users along the output supply chain. Our empirical application of the shared responsibility approaches focuses on CO2 emissions, using the 2005 world IO table available from WIOD. In the empirical tests of aggregation (in)variance of country-level shared responsibilities, it is found that the shared responsibilities are more robust to aggregation when the sharing parameters are pegged to distance rather than to value added or final demand. All in all, our results further substantiate the robustness of the shared responsibility accounting principle, and this is important if the principle is to become standard or alternative (complementary) reporting practice.